Managing the quality of functional surfaces and the processing performance products of the ceramic materials on the polishing operations of fixed abrasive - Kai Jian D. (Interactive science, 2023)
the theoretical and experimental results of the investigation of fixed abrasive polishing of ceramic are presented in the paper. The equations of the intensity of dispersion allowing to assess the performance and the accuracy of shaping by using related technological environment and the geometry of the lapping are given in the article.
Keywords: качество; керамика; прочность; скорость; quality; ceramics; speed; strength; доводка; съемка; polishing